2015
DOI: 10.1016/j.jcat.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of element spatial correlation in Mn-promoted Co-based Fischer–Tropsch synthesis catalysts

Abstract: a b s t r a c tMaking connections between performance and structure in bimetallic catalysts requires knowledge of how the two elements are spatially associated. Elemental maps obtained by analytical TEM methods are an invaluable tool for identifying the location of different elements, but for many samples, visual inspection of elemental maps is insufficient for assessing the degree of element spatial correlation. This is particularly true for beam-sensitive materials where short mapping acquisition times lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…The authors suggested that Mn facilitates the dissociation and disproportionation of CO and suppresses H 2 adsorption on the catalyst surface, thereby creating a relatively C-rich and H-lean surface chemical environment. Similar arguments were previously advanced by Johnson et al 30,31 to explain the high selectivity of C 5+ products and olefins, at the expense of methane. Overall, however, little is known about how the kinetics of the Co–Co 2 C phase transformation drive both reaction rate and selectivity.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The authors suggested that Mn facilitates the dissociation and disproportionation of CO and suppresses H 2 adsorption on the catalyst surface, thereby creating a relatively C-rich and H-lean surface chemical environment. Similar arguments were previously advanced by Johnson et al 30,31 to explain the high selectivity of C 5+ products and olefins, at the expense of methane. Overall, however, little is known about how the kinetics of the Co–Co 2 C phase transformation drive both reaction rate and selectivity.…”
Section: Introductionsupporting
confidence: 79%
“…In a previous study with Mn(II)-promoted Co/SiO 2 , Johnson et al 30,31 considered the high selectivity of C 5+ formation with their catalyst as being due to an increase of CO ad concentrations, i.e., a decrease of the H ad /CO ad ratios, following the strong Lewis acid–base interaction between Mn(II) and CO ad . While the present paper provides clear evidence for the partial pressure ratio P H2 /P CO to have a profound influence on the selectivity of the reaction, the amounts of Mn(II) (in MnO) or Mn(II)–Mn(IV) (in Mn 5 O 8 ) employed in our study are far beyond the low Mn(II) promoter concentrations in Co/SiO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, work by de Jong et al (4) (5) and Weckhuysen et al (6) (7) (8) (9) (10) has reported that promotion with MnO enhances the rate of CO consumption and C 5+ selectivity. Studies by these authors and others have shown that these effects are a consequence of good contact between metallic Co and MnO (11) (12).…”
Section: Introductionmentioning
confidence: 89%
“…Ali et al speculated that Co active sites at the interface with ZrO2 may exhibit enhanced activity toward CO hydrogenation (13), a hypothesis that originates from studies of metal oxide-promoted Rh catalysts (20) (21). This hypothesis has also been used to rationalize the catalyst structure-performance relationships resulting from Mn promotion of Co-based FTS catalysts (22) (23). In this study, we demonstrate that Zr promotes the catalyst activity and selectivity in a manner analogous to promotion by Mn.…”
Section: Introductionmentioning
confidence: 99%